Modelagem dinâmica da paisagem: o estudo de um pólo de fruticultura tropical na região semi - árida - Paim, Geovana Freitas (2008)
The loss of habitat in rain forests due to anthropic actions inspires research to evaluate the impacts on the highly modified landscapes. The Caatinga is a forest of ignored historic value which, nowadays, has several sites of degradation. This work aims at evaluating the influences of the increase in the use of the soil for agricultural proposes on the loss of Caatinga in Perímetro de Irrigação Maniçoba –PIM - (Maniçoba Irrigation Perimeter). The work also aims at drawing comparison between PIM landscape and its external landscape. PIM is located in the region called Médio São Francisco and it belongs to Juazeiro municipality in Bahia, Brazil. The area is famous for irrigated fruit production.. Previous researches point out the limitation in the service of pollinators in the area, indicating an association of this problem with the quality of the natural habitat. A landscape external to the PIM was used as control area due to its conservation condition. The study was carried out based on a LUCC (Land Use/Land Cover Change) model in order to relate it to the processes of global environmental changes. Maps of land use and cover have been produced by digital processing techniques for a multitemporal series of satellite images from the years of 1976, 1981, 1987, 1999 and 2006. The quantification of the changes occurred in the landscape was made through metric related to the Ecology of Landscape and compared with the external conditions of Perímetro Maniçoba (Maniçoba Perimeter). Moreover, it was produced the characterization of the occurred changes tendencies through the dynamic modeling of the landscape and also by observing the influences of static variables: Main river, secondary rivers, roads and urban areas. The model conducted the estimates of the occurred changes and simulations on the future evolution of the landscape. The results showed loss of 47% of the Native Vegetation for the expansion of crop areas in 30 years time. The quantity of fragments in the Caatinga in 1976 was low (less than 50). However this value increased 4 times from 1981 on, and in 2006 it had reached more than 200.Whereas the loss of natural vegetation in the external landscape was only 659ha and the level of fragmentation was low (less than 50) within the same period. The results of the landscape metrics showed that the external landscape does not present structural similarity compared to Perímetro Maniçoba, proving the system of intensive soil use. The dynamic modeling presented scenarios that show disorganized expansion of agriculture in the area, where the proximity to São Francisco River created a deforestation pattern for being a main agent in drought events. With the introduction of the irrigation system the deforestation pattern was conducted through the roads favoring population spread through the whole area, which caused deforestation of neighboring vegetation. The future landscape modeling presented optimistic expectations by 2016, indicating the regeneration of native vegetation. Despite the importance of scenarios simulation (because it offers annual spatial visualization of the changes) it will only become real if the forces that cause the changes continue at the same pace. Thus, the advance of the Caatinga observed in the future modeling means a chance of change, but not the only one. With the estimated loss of the Caatinga, it is believed that there was a reduction in its quality, as well as in local biodiversity and ecosystem services, specially pollinization.